2004
DOI: 10.1080/0955300042000213673
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchanges in ring chromosomes following X‐irradiation of human lymphocytes

Abstract: Single-chromatid rings visualized clearly using PCC techniques indicate SCE in the respective rings. Contrary to the conventional SCE-detecting technique, this approach does not require the use of bromodeoxyuridine, which itself leads to SCE. Some of the observed SCE might be secondary products resulting from the repair of radiation-induced DNA damage, while others may be spontaneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, extra fragments were detected at all doses, but in a similar way to rings, the frequency in G2/M-PCC cells was always significantly higher than in M cells. Higher frequencies of extra fragments in G2/ M-PCC cells to those in M-cells were also observed after X-or c-ray irradiation (Kovacs et al 1994;Kanda et al 2004;Puig et al 2013). Using pan-telomeric and pan-centromeric PNA probes it was reported that the G2/M checkpoint negatively selects cells with incomplete chromosome aberrations (Rodr ıguez et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, extra fragments were detected at all doses, but in a similar way to rings, the frequency in G2/M-PCC cells was always significantly higher than in M cells. Higher frequencies of extra fragments in G2/ M-PCC cells to those in M-cells were also observed after X-or c-ray irradiation (Kovacs et al 1994;Kanda et al 2004;Puig et al 2013). Using pan-telomeric and pan-centromeric PNA probes it was reported that the G2/M checkpoint negatively selects cells with incomplete chromosome aberrations (Rodr ıguez et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…After observation by AFM, some slides were destained with methanol/acetic acid, treated with RNase A, and processed for hybridization according to a dual staining method developed for the successive application of Giemsa staining and Xuorescence in situ hybridization (FISH) painting in the same metaphase [12][13][14]. The centromeric regions of all human chromosomes were labeled with biotinylated human pan centromeric chromosome paint (STAR FISH, Cambio, Cambridge, UK) conjugated with avidin-Xuorescein isothiocyanate (FITC) (Roche Diagnostics, Tokyo, Japan) according to the manufacturer's instructions.…”
Section: Fluorescence In Situ Hybridization Of Centromeresmentioning
confidence: 99%
“…Also, in chemically induced PCCs at G 2 phase, the centromeres are not clearly visible, thus making a G 2 -phase cell easily distinguishable from a metaphase cell [32]. Apart from calyculin-A, other phosphatase inhibitors have been used for the chemical induction of PCCs, such as okadaic acid [51,52,53]. However, it has been mentioned that the efficiency of the induction of PCC by calyculin-A is greater than that by okadaic acid [54].…”
Section: Chemically Induced Pccmentioning
confidence: 99%
“…The results demonstrated that chromosomal damage increased with LET in both interphase and metaphase cells, and that the number of chromosomal aberrations observed in interphase was threefold higher than in metaphase. Other scientific groups have combined chemically induced PCC in irradiated lymphocytes with pan-centromeric FISH in order to examine whether X-rays induce SCEs in ring chromosomes [51]. Gotoh and Asakawa [66] used okadaic acid-induced PCC in combination with chromosome painting to detect and evaluate chromosomal aberrations induced by high doses (>40 Gy) of γ-irradiation.…”
Section: Biodosimetry and Biomonitoring Of Exposure To Ionizing Radiamentioning
confidence: 99%
See 1 more Smart Citation